Safety and effectiveness of Phoenix atherectomy for endovascular treatment in calcified common femoral artery lesions - Kronlage, Mariya; Erbel, Christian; Lichtenberg, Michael Klaus William; Heinrich, Ulrike; Katus, Hugo; Frey, Norbert; Giusca, Sorin; Korosoglou, Grigorios (Vasa, 2021)
Summary:Background: Traditionally endarterectomy has been considered as the gold standard technique for the treatment of common femoral artery (CFA) lesions. The aim of this study is to investigate the procedural safety and mid-term outcomes of minimal invasive Phoenix atherectomy for the treatment of CFA lesions. Patients and methods: Phoenix atherectomy was used for treatment of 61 consecutive, moderately to heavily calcified CFA lesions in 56 patients. Lesions were classified based on the CFA occlusive disease classification (Type I, II&III lesions). Primary endpoints were technical, procedural, and clinical success rate. Safety endpoints (vessel perforation, peripheral embolization) and clinically driven target lesion revascularization (TLR) were also assessed. Results: Of 61 CFA lesions, 58 (95%) exhibited at least moderate/severe calcification (PACSS3 in 38 (62%) and PACSS4 in 20 (33%) cases). Type III lesions were present in 30 (49%), type I/II lesions in 31 (51%) cases. Technical and procedural success was achieved in 30 (49%) and all 61 (100%) lesions, respectively with low complication rates (0% perforation, 2% embolization). Adjunctive treatment after atherectomy was performed using drug-coated balloon (DCB) in 35 (57%) and bail-out stenting in 6 (10%) cases. Target lesion revascularization (TLR) occurred in 4 (7%) cases during a mean follow-up duration of 11±7months. All patients exhibited clinical improvement at follow-up, showing mean Rutherford category reduction from 3.7±1.1 to 1.5±1.1 (p<0.001). Conclusions: The Phoenix device can be used for the effective endovascular treatment of CFA lesions, due to its reasonable safety profile and mid-term results.